Penerapan Media PPT Interaktif Melalui Pendekatan CRT untuk Meningkatkan Hasil Belajar Matematika Kelas 1 di SDN Putat Jaya IV-380 Surabaya - Gretta Misselya Nora; Desi Eka Pratiwi; Herlia Nimas Ayu Hastungkoro (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to improve the learning outcomes of grade 1 students at SDN Putat Jaya IV-380 Surabaya on addition material through the use of interactive PPT media with a Culturally Responsive Teaching (CRT) approach. This research is Classroom Action Research (PTK) with 28 students as subjects. The data collection techniques used are observation and tests. In cycle I, teacher teaching activities and student learning were in the sufficient category, respectively with a percentage of 71.43% and 68.18%, and the completeness of student learning outcomes was 68.18% (poor category). In cycle II, teacher teaching activities and student learning increased to 94.64% and 95.45% (very good category), and the average student learning outcomes increased to 89% (very good category). The research results show that the application of interactive PPT media through the CRT approach can improve the learning outcomes of grade 1 students on addition material.